Neo Tropicália : When Lives Become Form : Contemporary Brzilian Art : 1960s to the Present. - Chaimovich, Felipe; Hasegawa, Yuko; Herkenhoff, Paulo; Ichikawa, Akiko; Nakahara, Jin; Namba, Sachiko; Suga, Keijiro (Tokyo : Museum of Contemporary Art, 2008)
Oiticica, Hélio ; Clark, Lygia ; Pape, Lygia ; Schendel, Mira ; Ohtake, Tomie ; Bardi, Lina Bo ; Ohtake, Ruy ; assume vivid astro focus ; Mano, Rubens ; Neto, Ernesto ; Degaki, Rogério ; Marepe ; Koch, Lucia ; Tavares, Ana Maria ; Neuenschwander, Rivane ; Leonilson ; Milhazes, Beatriz ; Montijo, Guilianno ; Meireles, Cildo ; Verzuti, Erika ; Bispo do Rosário, Arthur ; Komatsu, André ; Muniz, Vik ; Osgemeos ; Campana Brothers ; Fraga, Ronaldo ; Capeto, Isabela ; Nakao, Jum
biog. p.190-197
Engels
Japans
Neo Tropicália : When Lives Become Form : Contemporary Brailian Art : 1960s to the Present, Hiroshima City Museum of Contemporary Art Hiroshima, 22.10.2008 - 24.01.2009 /MOT (Museum of Contemporary Art Tokyo), 12.01.2009 - 01.03.2009
boek
Keywords: Brazilië